2011
DOI: 10.1002/lary.21809
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of pepsin in laryngeal mucosa for diagnosing laryngopharyngeal reflux

Abstract: Pepsin IHC staining of the laryngeal mucosa appears to be a sensitive and specific test for diagnosing LPR in a clinical application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 17 publications
2
71
0
Order By: Relevance
“…Gastric contents include pepsin but not acid in every reflux episode; regarding this, several studies show that acid does not damage the mucosa by itself. These studies state that pepsin plays the key role in mucosal injury, which can explain the mechanism of injury in the laryngeal mucosa in non-acidic reflux (25). Moreover, laryngeal epithelium has been shown to be more sensitive to the damage caused by pepsin than esophageal epithelium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastric contents include pepsin but not acid in every reflux episode; regarding this, several studies show that acid does not damage the mucosa by itself. These studies state that pepsin plays the key role in mucosal injury, which can explain the mechanism of injury in the laryngeal mucosa in non-acidic reflux (25). Moreover, laryngeal epithelium has been shown to be more sensitive to the damage caused by pepsin than esophageal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…However, the false negative results obtained via pH monitoring is within the range of 15 to 30% (17). pH monitoring is an invasive and expensive method which may be difficult to use in practice (18,19). Knight et al (15) reported that approximately 12% of patients do not tolerate this test.…”
Section: Discussionmentioning
confidence: 99%
“…Rarer but more serious manifestations or complications associated with LPRD include laryngospasm and laryngeal cancer (14,18). Several tests have been used to diagnose LPRD and these include: Reflux Symptom Index (RSI), Reflux Finding Score (RFS), Double probe pH monitoring, Pepsin (sputum) as a marker of LPR, Sensory testing; Laryngopharyngeal sensory descrimination testing (FEESST), Esophagoscopy, Barium esophagography and Bernstein acid perfusion (19)(20)(21)(22)(23). The reflux symptoms Index was described by Belfaski as a compilation of nine reflux related laryngeopharyngeal symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of pepsin in the laryngopharynx has also been shown to correlate with reflux events [17] and has been found in the laryngeal epithelial mucosa of patients with reflux-attributed laryngeal disease [18,19]. Pepsin has been identified in the sputum and bronchoalveolar lavage fluid of patients with chronic cough and LPR [6,20], and it has been used to indicate aspiration in patients with lung allografts [21] and the effectiveness of anti-reflux surgery [22].…”
Section: Introductionmentioning
confidence: 97%